Perception of the Internet of Things in consumer applications in the context of intergenerational differences - Kalińska-Kula, Magdalena; Wyciszkiewicz, Aleksandra (Postrzeganie Internetu Rzeczy w zastosowaniach konsumenckich w kontekście różnic międzypokoleniowych, 2020)
The article attempts to determine how members of different generations perceive the Internet of Things (IoT) in consumer applications, and whether despite its growing popularity, intergenerational differences in terms of the perception of IoT technology are significant. An intergenerational comparative analysis was conducted based on CAWI study results. The data for the analysis came from a sample of 241 respondents. In light of the obtained results, the hypothesis assuming that members of individual generations differ significantly in terms of the perceived utility of the IoT devices in consumer applications was not confirmed. The influence of age as a variable differentiating the perception of possibilities of application of the Internet of Things in various economic sectors was also not confirmed.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 9, s. 57-70
Keywords: Internet of Things; IoT; generations; intergenerational differences